STUDI TENTANG EFEKTIVITAS TADARUS AL-QUR`AN DALAM PEMBINAAN AKHLAK DI SMPN 8 YOGYAKARTA - Muhammad Noer Cholifudin Zuhri (Cendekia: Kependidikan dan Kemasyarakatan, 2013)
A habit-forming activity of Tadarus in SMP N 8 Yogyakarta is an essential and integral part of other activities to build noble characters among students, such as prayers, praying together, living clean, discipline, class duty, flag ceremonies and charity work. Having regular activity of Tadarus in public school attracts many attentions to study it in greater depth. By employing naturalistic qualitative approach, this research was aimed to reveal the background and implementation of Tadarus and its effectiveness as a mean of students’ morals building.The results showed that, firstly Tadarus was held regularly every morning about 15 minutes before the first period. The school principal was in charge of the activity, while the religion teacher functioned as a coordinator to run the program helped by all teachers of SMP N 8 Yogyakarta. Secondly, Tadarus al - Qur`an was proven effective to build students’ morals. The effectiveness could be seen from several aspects, such as: 1) aspect of the duty and function, in which the teacher had taken the roles as a supervisor and guide on the process of activities, in other hand, students showed responsibility to carry out the activities seriously, 2) planning/ program, Tadarus became an integral part of school activities that had been well-prepared and organized systematically, 3) provisions/rules, it had been conducted by using well-organized techniques, and 4) aspect of goals, the ultimate objective of Tadarus had been achieved that was equipping students with a commendable character and far from despicable character. كان تعويد نشاط "تدارس القرآن" في المدرسة المتوسطة العامة الحكومية جوكجاكرتا عنصرا مهما لتكوين الأخلاق الكريمة بجانب الأنشطة الأخرى مثل صلاة الجماعة، والذكر جماعيا، والمحافظة على النظافة، والانضباط، وتقسيم الوظيفة في الفصل، ونشاط المراسم، والإنفاق. وأصبح نشاط "تدارس القرآن" جذابا للدراسة والبحث فيه. حاول هذا البحث – بالمدخل الكيفي الطبيعي – للكشف عن الخلفية وتطبيق نشاط "تدارس القرآن – وفعّاليته كوسيلة لتكوين الأخلاق الكريمة. نتائج هذه الدراسة هي : أولا، عقد هذا النشاط لمدة ربع ساعة قبل الحصة الأولي، والمسؤول هو رئيس المدرسة ومدرس الدين الإسلامي كالمنظم والمدير والقائم به جميع مدرس المدرسة المتوسطة العامة الحكومية 8 جوكجاكرتا. ثانيا، كان هذا النشاط فعّالا في تكوين أخلاق الطلاب. وهذه الفعالية تظهر في الجوانب التالية : 1) الوظيفة والدور. قام المدرسون بدور التفتيش، والمرافقة، وأدى الطلاب هذا النشاط باهتمام ووعي. 2) الخطة أو النشاط. أصبح هذا النشاط نشاطا مدرسيا روتينيا مبرمجا. 3) النظام. عقد هذا النشاط بأسلوب وتنفيذ مبرمج واضح، 4) الهدف، والهدف من هذا النشاط غرس الأخلاق الكريمة في نفوس الطلاب وإبعادهم عن ضدها.